Preparation and characterization of a solid polymer electrolyte PEO-ENR50 (80/20)-LiCF3SO3 - Noor S.A.M.; Ahmad A.; Rahman M.Y.A.; Talib I.A. (2023)
The preparation and characterization of a polymer electrolyte films containing 80 wt % of poly (ethylene oxide) (PEO) and 20 wt % epoxidized natural rubber (ENR50) complexed with LiCF3SO3 has been reported. The ac impedance data showed good conducting properties of the solid polymer electrolyte (SPE) films. The greatest room temperature ionic conductivity of 7.5 10-5 S cm-1 was obtained at 25 wt % of LiCF 3SO3 salt. This result has been supported by differential scanning calorimeter and X-ray diffraction analysis. Analysis differential scanning calorimetry showed the relative percentage of crystallinity and T m of PEO decreased with the increasing wt % of LiCF 3SO3. Analysis with X- ray diffraction suggested that the semicrystalline nature of PEO turned to amorphous due to the presence of LiCF3SO3. 2009 Wiley Periodicals, Inc.